2011
DOI: 10.1111/j.1474-9726.2011.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired IGF1R signaling in cells expressing longevity-associated human IGF1R alleles

Abstract: SummaryDampening of insulin ⁄ insulin-like growth factor-1 (IGF1) signaling results in the extension of lifespan in invertebrate as well as murine models. The impact of this evolutionarily conserved pathway on the modulation of human lifespan remains unclear. We previously identified two IGF1R mutations (Ala-37-Thr and Arg-407-His) that are enriched in Ashkenazi Jewish centenarians as compared to younger controls and are associated with the reduced activity of the IGF1 receptor as measured in immortalized lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 10 publications
4
81
0
2
Order By: Relevance
“…Using this population, we have successfully identified longevity associated-phenotypes, -genotypes, and their association with health outcomes (Atzmon et al, 2006; Barzilai et al, 2006; Barzilai et al, 2003). In particular, we identified two rare missense variants in the IGF-1 receptor gene (IGF1R) that were enriched in Ashkenazi Jewish centenarians as compared to younger elderly and we further showed that they were true reduced-function variants (Suh et al, 2008; Tazearslan et al, 2011). These results highlight the value of resequencing candidate genes in our Ashkenazi Jewish centenarian cohort to identify clinically relevant targets in humans.…”
Section: Descriptionmentioning
confidence: 89%
“…Using this population, we have successfully identified longevity associated-phenotypes, -genotypes, and their association with health outcomes (Atzmon et al, 2006; Barzilai et al, 2006; Barzilai et al, 2003). In particular, we identified two rare missense variants in the IGF-1 receptor gene (IGF1R) that were enriched in Ashkenazi Jewish centenarians as compared to younger elderly and we further showed that they were true reduced-function variants (Suh et al, 2008; Tazearslan et al, 2011). These results highlight the value of resequencing candidate genes in our Ashkenazi Jewish centenarian cohort to identify clinically relevant targets in humans.…”
Section: Descriptionmentioning
confidence: 89%
“…71 These mutations have been shown to suppress IGF-1 signalling and decrease transcription of target genes. 71 Female carriers of these mutations have high IGF-1 levels and slightly short stature, which implies that they are IGF-1-resistant. 72 These studies provide evidence that reduced IGF-1 signalling can positively affect human lifespan.…”
Section: Igf-1 and Longevitymentioning
confidence: 99%
“…Nonagenarian female carriers of genetic polymorphisms that attenuate the action of the GH/IGF-1 pathway exhibit longer survival (van Heemst et al, 2005). Likewise, individuals with exceptional longevity are enriched with functional mutations in the IGF1R gene, which confer partial IGF-1 resistance (Suh et al, 2008; Tazearslan et al, 2011). Variants in AKT1 and FOXO3A genes, which are elements of the GH/IGF-1 signaling pathway, have been identified in long-lived individuals from several different cohorts of diverse ethnic backgrounds, although their functional role has not yet been defined (He et al, 2014; Pawlikowska et al, 2009).…”
Section: Human “Models” Of Gh/igf-1 Attenuation and Agingmentioning
confidence: 99%